Design a Reactive Power Compensator in Smart Home under Variation of Supply Voltage of Low-Level Distributed Power System - Fadhil T. Aula (Zanco Journal of Pure and Applied Sciences, 2022)
Reactive power compensation is an essential goal for building smart homes when they are supplied from inconsistent voltage sources such as local diesel generators. These houses are subscribing to these generators with limited amperes. While the active power cannot be reduced as home appliances are necessary for daily life, therefore, the focus is on reactive power to be managed. The challenge of dealing with this problem is worsened when the supply voltage is unstable and varies with the time as local diesel generators behave. In this paper, a compensation technique is presented using a modified dynamic capacitor method in which the value of the capacitor is varied and controlled through switching operations. A Matlab/Simulink showed the effectiveness of the proposed technique in compensating the reactive power as well as reducing amperes for different cases of real situations.